Study on Ergonomic and Crew Protective Interventions on Light Armoured Vehicles for Ethiopian Army - Mengistu, Amare Wibneh (My University, 2022)
Light armored vehicles (LAVs) are multi-purpose type of vehicles. It can be used for reconnaissance activities such as patrolling and scouting activities, transporting and carrying troops, ambulance service, small and large scale combating activities in various army wings, and conflict cessation in streets and institutions of urban or city. From the design perspective, LAVs require maneuverability, survivability, off-road efficiency, and compact size, maintaining the adequacy of the space and comfort. Researchers have conducted various studies regarding its maneuverability, survivability/crew protection, and firing power in a compact interior space of the vehicle. However, ergonomics aspects are often overlooked while space compactness and crew protective aspects are considered. Therefore, the current research aims to investigate the design intervention of the ergonomic and crew protective aspects without affecting the space occupancy and mobility of the Ethiopian LAV to enhance crew comfort and safety.
Karmakar, Sougata
Keywords: Ergonomic Design; Anthropometry; Vehicle Design; Hull Obliquity; Digital Mock-ups; Physical Trial; DHM; Vehicular Accommodation; Crew Protection; PCA